Indeks Massa Tubuh Awal Kehamilan Ibu sebagai Indikator yang Paling Berperan terhadap Kenaikan Berat Badan Ibu Selama Hamil - Zuhairini, Yenni; Kasmanto, Hendro; Nugraha, Gaga Irawan (Faculty of Medicine, Universitas Padjadjaran, 2016)
Berat bayi lahir rendah dipengaruhi oleh kenaikan berat badan ibu selama hamil. Penelitian ini bertujuan mencari indikator status gizi ibu trimester pertama yang paling berperan terhadap kenaikan berat badan ibu selama hamil. Kohort ini dilakukan selama tahun 2014 yang merupakan bagian dari Tanjungsari Cohort Study di Jawa barat. Variabel status gizi ibu trimester pertama (indeks massa tubuh (IMT), massa lemak (ML), massa lemak bebas (MLB), lingkar lengan atas (LLA)) dihubungkan dengan kenaikan berat badan (BB) ibu selama hamil dari trimester pertama sampai ketiga dengan analisis bivariat Pearson dilanjutkan dengan regresi linier multivariat. Perbedaan kenaikan berat badan ibu selama hamil pada tiap kelompok dengan uji ANOVA satu arah. Perubahan asupan energi dan protein diuji dengan uji T independen pada semua kelompok. Diperoleh 37 subjek yang telah mencapai trimester ketiga menunjukkan korelasi antara IMT, ML, MLB, LLA dengan kenaikan BB ibu selama hamil. Terdapat hubungan negatif IMT dengan KBB (p=0,002 dan r2=0,234). Kenaikan berat badan ibu selama hamil pada IMT kurang, normal, overweight, obes 1 dan obes 2 masing-masing 7,38; 8,54; 6,73; 4,38 dan 3,30 kg. Perubahan asupan energi dan protein pada subjek dengan IMT tinggi dan rendah masing-masing p=0,09 dan p=0,96. Simpulan, indeks massa tubuh ibu trimester pertama merupakan indikator yang paling berperan terhadap kenaikan berat badan ibu selama hamil, IMT berbanding terbalik dengan kenaikan berat badan ibu selama hamil kecuali pada IMT kurang. [MKB. 2016;48(3):171–5]Kata kunci: Ibu hamil, indeks massa tubuh, kenaikan berat badan Body Mass Index in Early Pregnancy as the Most Contributing Indicator for Weight Gain during Pregnancy Low birth weight is influenced by maternal weight gain during pregnancy. This study aimed to reveal the most contributing pre-pregnancy maternal nutritional status indicators pre- that are responsible for maternal weight gain during pregnancy. This study was carried out during the year of 2014 and was performed as a part of Tanjungsari Cohort Study in West Java. The pre-pregnancy maternal nutritional status variables (body mass index (BMI), fat mass (FM), fat free mass (FFM), and mid upper arm circumference (MUAC)) were associated with the gestational weight gain (GWG) of pregnant women from the first to the third trimester using Pearson bivariate analysis followed by multivariate linear regression. The difference of GWG in each group was analyzed using one-way ANOVA test, while changes in energy and protein intake were tested using independent T test in all groups. From 37 subjects who had reached the third trimester, it was shown that there was a correlation of BMI, ML, MLB, and LLA to GWG. Themultivariate analysis showed a negative correlation between BMI and GWG (p=0.002 and r2=0.234). Maternal weight gain during pregnancy in underweight, normal weight, overweight, obese 1, and obese 2 women were 7.38, 8.54, 6.73, 4.38, and 3.30 kg, respectively, while changes in energy and protein intake in subjects with high and low BMI were p=0.09 and p=0.96, respectively. In conclusion, the pre-pregancy maternal body mass index is the most contributing indicator for maternal weight gain during pregnancy, BMI is inversely related to maternal weight gain during pregnancy, except in the underweight group. [MKB. 2016;48(3):171–5]Key words: Body mass index, gestational weight gain, pregnant women